(untitled) (Journal of actual problems of jurisprudence, 2023)
The internationalization of education is among the current trends in the field of higher and professional education in the Republic of Kazakhstan. Teaching in an intercultural classroom is undoubtedly appealing with its pedagogical novelty. At the same time, it reveals a number of new didactical challenges. Teachers face new issues concerning the optimal balance between different linguistic and cultural rights in the educational process entailing foreign students. From a conceptual point of view, knowing how to resolve these issues is one of the elements of intercultural communicative competence, which the authoritative author Darla Deardorff claims that university teachers should possess. Thus, the purpose of the article is to identify and analyze which key legal categories the Ministry of Education of the Republic of Kazakhstan resorts to when answering citizens’ addresses about how intercultural conflicts should be resolved in the educational process. This article contributes to a theoretical understanding of intercultural communicative competence by clarifying the national context of those legal categories which are employed for resolving intercultural issues in education in Kazakhstan. Although the analysis relates to compulsory and professional education, its undisputed novelty is in working with primary data recovered from the full-text responses of the national ministry to citizens’ questions. Analyzing fifteen full-text answers to citizens’ addresses by virtue of the method of qualitative content analysis, we were able to identify several key legal categories that are used in resolving intercultural issues in education. The explanation of findings shows a partial correspondence with modern theories of human rights in the intercultural educational environment. Key words: intercultural communicative competence; diversity in education; linguistic, cultural and religious rights in education; equality and non-discrimination